INSTYTUCJA PRAWNA ZATRUDNIENIA ZARZĄDCY ZAKŁADU PRACY W PERSPEKTYWIE KODYFIKACJI PRAWA PRACY - Kijowski, Andrzej; Jankowiak, Jarosław (Wydział Prawa i Administracji UAM, 2006)
The paper addresses a fundamental issue which is the determination of the working or employment status of a managing director. It attempts to answer the question whether such a person de lege ferenda should be given the status of an employee (on a contract of service) or a non-employee (a worker on a contract for services). In order to answer this question the authors first analyse the course and results of a discussion that went on in Poland’s interwar period (1919-1939), then look at the existing regulations and solutions in other states, and finally analyse the tendencies currently present in Polish labour law, to conclude that despite numerous convincing arguments to the contrary, pragmatic reasons speak for securing for a managing director a status or an employee, which conclusion is also a recommendation for consideration when drafting an amended version of labour law in Poland. The same arguments, in the authors’ opinion, speak against the same status for a managing director to be provided for in the potentially drafted EU labour law model.
THE LEGAL INSTITUTION OF EMPLOYMENT OF A MANAGING DIRECTOR IN THE LIGHT OF THE CODIFICATION OF LABOUR LAW